Exploring versatile applications of cyclodextrins: an overview. (23rd March 2016) - Sharma, Neha; Baldi, Ashish
Abstract: Context : Ever since the discovery of cyclodextrins, a family of cyclic oligosaccharides based on α (1 → 4) linkage among glucopyranose subunits, these versatile supramolecular hosts have received tremendous attention for scientific explorations. Due to their property of forming host–guest type inclusion complex, cyclodextrins and their synthetic derivatives exhibit wide range of utilities in different areas viz . pharmaceuticals, drug delivery systems, cosmetics, food and nutrition, textile and chemical industry etc. Objective : The purpose of this review is to highlight properties, advantages, recent studies and versatile benefits of cyclodextrins and to re-strengthen their prospective applications in novel directions for future research. Methods : This article summarizes a variety of applications of cyclodextrins in various industrial products, technologies, analytical and chemical processes and recent industrial advancements by extensively literature search on various scientific databases, Google and websites of various associated pharmaceutical industries and patenting authorities across the world. Results and conclusion : Due to possibility of multidimensional changes in physical and chemical properties of molecules upon inclusion complexation in cyclodextrins, these compounds are of great commercial interest and may offer solution to many of the scientific problems of the current world.